Intercultural competences of teachers with immigrant students in the Basque Country - Félix Etxeberría Balerdi; Iñaki Karrera; Hilario Murua (Revista Electrónica Interuniversitaria de Formación del Profesorado)
This paper examines the responses of 200 teachers in Bilbao and Donostia (Spain) in regard to their own competences in teaching immigrant school children. Teachers say that they have great awareness and remarkable attitudes, but they have less developed competences relating to knowledge and skills in dealing with immigrant students. In relation to their personal situation, educators indicate low levels of satisfaction, of expectations and of professional training, and feelings of abandonment, of neglect and of lack of knowledge on how to address the task of educating immigrants. Teachers affirm that they know there are resources and mechanisms available to face intercultural education and they valued them positively, although they considered them insufficient.